Plating in diaphyseal fractures of the forearm - Iacobellis, Claudio; Biz, Carlo (Acta Biomedica Atenei Parmensis, 2014)
Background and aim of the work: Currently, open reduction and internal plate-screw fixation is generally accepted as the gold standard treatment of diaphyseal forearm fractures. The purpose of this retrospective study was to evaluate the clinical and radiographic outcomes of open reduction and internal fixation by using the Locking Compression Plate (LCP) implant system of radial, ulnar or combined shaft fractures of a skeletally mature patients group treated at our institution. Methods: We examined 47 patients, 44 men and 3 women, mean age 35 years (range 14–74) operated for diaphyseal fractures of the forearm. Overall 64 segments were treated: 32 ulnar and 32 radial. All patients received 3.5-mm titanium LCPs (Locking Compression Plates) with “combi-holes”. Follow-ups included standard X-rays and clinical assessment according to Anderson’s criteria and the DASH questionnaire. Results: Mean follow-up was 11 months (range 6-39). The number of the patients who achieved complete consolidation was 43 with a union rate of 91.5%. They showed 37 excellent results and 6 satisfactory results according to Anderson criteria, while non-union occurred in 4 out of 64 segments (2 ulnar and 2 radial) with a non-union rate per patient of 8,5%. The mean score of the DASH scale was 13.5 (range 0-46.7). Conclusions: Our data show that internal plating gives good functional outcomes in the treatment of forearm diaphyseal fractures, as long as the surgical technique is perfect and carried out by expert surgeons. However, further research is desirable to better identify fracture types for which LCPs should be used.